Refractory Giardiasis in an Immunosuppressed Patient in Turkey - Filiz Kaya; Ahmet Çağkan İnkaya; Salih Maçin; Yakut Akyön; Sibel Ergüven (Journal of Infection in Developing Countries)
Giardiasis is an infection of the small intestine caused by the protozoan parasite Giardia duodenalis. In immunocompetent patients the infection is usually self-limited and no treatment may be needed. Immunodeficiency, however, is a predisposing factor for the development of severe Giardia infection. In this report, a case of recurrent giardiasis refractory to nitroimidazoles and nitazoxanides presented. A 28-year-old male patient with hypogammaglobulinemia admitted to our hospital because of chronic diarrhoea. Microscopic examination of stool revealed a high number of Giardia trophozoites and cysts. Treatment with higher doses and a longer course of metronidazole, trimethoprim-sulfamethoxazole, ornidazole and albendazole failed. Administration of nitazoxanide, which has been reported to be effective against Giardia duodenalis refractory to nitroimidazoles, was commenced, but his symptoms persisted and stool samples demonstrated Giardia trophozoites and cysts again.